Unusual staphylococcal toxic shock syndrome presenting as a scarlet-like fever - Andrey, D.O. (New Microbes New Infect, 2015)
Diagnosis of nonmenstrual staphylococcal toxic shock syndrome (TSS) is often challenging. A female medical colleague had a rare entity, a staphylococcal pharyngitis complicated by TSS. The diagnosis was confirmed by isolation of tst-positive Staphylococcus aureus in throat culture and by identification of a specific Vβ2 expansion pattern of her T lymphocytes. Recent improvements in microbiology can be of great help for the diagnosis of nonmenstrual TSS.